The Multi-dimensions of Teachers’ ICT learning - Adi Suryani; Soedarso Soedarso; Niken Prasetyowati; Umi Trisyanti (Research and Development Journal of Education, 2021)
Todays’ teachers should respond to their students’ learning need in this digital era, but frequently they do not know how to operate technology. This situation imposes teachers  to survive and grow through self-learning and learning method discovery instead of relying on formal training. This study aims to explore how teachers survive and perform their self-learning. The data are collected from an interview with a senior teacher from higher education institution and twenty-six senior high school teachers’ written responses. The data show that ICT learning requires the integration of affective, social and cognitive functioning through the process of adaptive learning from authentic environment, individual continuous and group learning. The study shows that teachers are potential adaptive learners, who learn from diverse everyday situations. They are engaging in situated learning process. ICT learning workshops are not the only platforms where they can learn ICT. On daily basis, the teachers learn from other more competent teachers, teachers learning communities and their own students